IMPLEMENTATION OF GAMIFICATION IN M-LEARNING ENGLISH APPS USING OCTALYSIS FRAMEWORK (CASE STUDY: MTS DEVELOPMENT UIN JAKARTA) - Fitri Mintarsih; Difa Risalah Akbar; Victor Amrizal; Hendra Bayu Suseno; Tjut Awaliyah Zuraiyah (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2025)
Studying and mastering the English language is highly important in the current era of globalization. Considering that the influence of globalization has expanded into various fields such as technology, economy, politics, trade, and more. Technology plays a crucial role in understanding and keeping up with changes in the era of globalization. It helps us acquire information, communicate, enhance productivity, expand opportunities, and adapt to changes. The advancement of information technology has entered various aspects of life, including the field of education. Smartphones are one of the widely favored information technology devices, and Android, as the most widely used smartphone operating system, holds a global market share of 70.48%. There are various learning applications on the Google Play Store, but these apps tend to have monotonous and less interactive content, leading users to quickly feel bored. To address these challenges, this research proposes a solution through the implementation of gamification in English language learning applications. Gamification is a concept aimed at enhancing motivation and learner engagement. The researcher uses the Octalysis Framework as a method or framework for designing effective gamification. The researcher selects Madrasah Tsanawiyah Pembangunan UIN Jakarta as the testing ground for the created application. The User Acceptance Testing (UAT) results reach a score of 83.7, interpreted as 'Very Good.' Post-application usage evaluation also indicates an 18% increase in student motivation. These results show that the M-Learning English application with a gamification approach using the Octalysis Framework can facilitate the learning process, meet the needs of teachers at Madrasah Pembangunan UIN Jakarta, and enhance student motivation and interest in learning.